Improved performance of P3HT:PCBM-based inverted organic solar cell using SnO2/ZnO electron transport bilayer for low light application - Noorakmar Hidayah Mohamed Hashini,; Mohammad Hafizuddin Hj Jumali,; Chi, Chin Yap (Penerbit Universiti Kebangsaan Malaysia, 2025)
Organic solar cells (OSCs) have attracted much research attention due to their advantages such as low cost, easy processing, light weight, flexible and suitable for large-scale production. ZnO has shown to be an effective electron transport layer (ETL) in OSCs. However, it also suffers from various defects on its surface and improperly matched work function with the photoactive layer which then hinders electron extraction and conduction in OSCs. Hence, in this work, due to its favorable attributes such as high electron mobility, wide bandgap as well as deep conduction and valence band, SnO2 was chosen in this study as cathode interfacial layer placed in stacked structure with ZnO. This study intends to improve the power conversion efficiency (PCE) of poly(3-hexylthiophene-2,5-diyl) (P3HT): (6,6)-phenyl-C61-butyric-acid-methyl-ester (PCBM) based inverted OSCs by exploiting the properties of SnO2 and ZnO as bilayer ETL. The ETL was inserted between transparent fluorine-doped tin oxide (FTO) and P3HT:PCBM photoactive layer. Experimental analysis of the different configurations of ETL (ZnO only, SnO2/ZnO, and ZnO/SnO2) toward the PCE of inverted type OSCs was presented. The SnO2 layer was synthesized via sol-gel spin coating method. Under both 1-Sun and white LED illumination, the devices with SnO2/ZnO ETL demonstrated the highest PCE of 1.01% and 1.62%, respectively, with 63% and 30% enhancement compared to the control device with ZnO only ETL. Our results suggest that by depositing the SnO2 layer before the ZnO layer, it can enhance the optical transmission, decrease the surface roughness and provide a well-matched energy level.